Structural Conformation Comparison of Different Clear Aligner Systems: An In Vitro Study - Aseel Alhendi; Rita Khounganian; Raisuddin Ali; Saeed Ali Syed; Abdullazez Almudhi (MDPI AG, 2022)
The aim of this study was to evaluate the structural conformations of three clear aligner systems, Eon®, SureSmile®, and Clarity®, and compare them with the most commonly used system, Invisalign®. Clear aligner samples from Invisalign®, Eon®, SureSmile®, and Clarity® were cut into 5 × 5 mm squares and exposed to artificial saliva for 2 weeks. The specimens were then subjected to a Vickers hardness test by applying three separate indentations with a 25 gf load for 15 s. Hardness was calculated using the following formula: Vickers hardness number = 1.854 (F/D2). Fourier transform infrared spectroscopy (FTIR) analysis was performed, with a diamond hemisphere and infrared beam being allowed to pass through each specimen. A mid-infrared range from 4000 to 375 cm−1 was recorded. The samples were also evaluated using scanning electron microscopy (SEM) combined with energy-dispersive X-ray microanalysis spectroscopy at different magnifications. No statistically significant differences were observed between the included systems with regard to hardness. All systems showed a polyurethane-based material, as illustrated by the FTIR analysis. Some structural variations were noted in the Invisalign® system, which had a more homogeneous architecture. Statistically significant differences in the carbon weights were found among the systems. The four systems presented comparable hardness levels. Mild molecular composition differences were found, but all systems had the similarity of being composed of a polyurethane-based material. Carbon and oxygen were the main elements, as they were located in all studied clear aligners. The SEM analysis revealed that Invisalign® had a smoother surface than the other three systems. All included clear aligners had similar characteristics with minimal differences, providing a wide variety of options for clinical orthodontic treatment according to patients' demands.